GREEN SYNTHESIS OF COPPER NANOPARTICLES FROM MYRTUS COMMUNIS LEAVES EXTRACT: CHARACTERIZATTION, ANTIOXIDANT AND CATALYTIC ACTIVITY - Al-Jubouri, A. K.; Al-Saadi , N. H.; Kadhim, M. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
A simple, cost-effective, and environmentally friendly method for making green nanoparticles has been developed. The current study examines the use of M. communis leaves extract in the biosynthesis of copper nanoparticles (CuNPs). The color change and UV-visible spectrophotometer, which showed a distinct peak at 481nm, confirmed the formation of these particles. Different techniques were used to characterize copper nanoparticles. The influential functional groups that can bio-reduce the copper ion Cu2+ were identified using Fourier Transform Infrared (FT-IR) spectroscopy. The crystal structure of copper nanoparticles was determined using X-ray diffraction (XRD), as evidenced by the peaks at 2θ values of 43.35, 50.50, and 74.21. In transmission electron microscopy (TEM), the particles have spherical morphology with an average diameter of 35–75 nm, while scanning electron microscopy (SEM) reveals the sphere-like shape of CuNPs. Copper-NPs synthesized in this study were tested as antioxidant and catalytic substances. CuNPs had superior radical scavenging activity when compared to an extract from Myrtus communis leaves. It is common to use 4-nitrophenol (4-NP) as a model reaction to evaluate synthesized nanomaterials’ catalytic properties. borohydride (BH) was found to bind to the surface of CuNPs, indicating that it is an adsorbent. As the BH concentration increased, we observed a blue shift in the surface plasmon resonance (SPR) of CuNPs. These shifts increase in direct proportion to BH concentration, as does 4-NP to 4-amino phenol (4-AP) conversion. Accordingly, CuNPs have better catalytic activity than extract at higher BH concentrations.